2011
DOI: 10.1039/c0jm03948a
|View full text |Cite
|
Sign up to set email alerts
|

Improving silica matrices for encapsulation of Escherichiacoli using osmoprotectors

Abstract: The development of sol-gel based processes for the encapsulation of living cells is a challenging task where the host material must be optimized both in terms of intrinsic properties and impact on cell viability. Here, the mechanical stability of silica hosts obtained via a mixed aqueous route based on sodium silicate-silica nanoparticle mixtures could be improved by increasing the relative content of molecular precursors over colloidal silica. The specific surface area, pore volume and diffusion properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 28 publications
5
27
0
Order By: Relevance
“…a). These data agreed well with previous reports (Perullini et al, ) showing that inclusion of SNPs in the alkoxide gels negatively impacts the gel mechanical properties.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…a). These data agreed well with previous reports (Perullini et al, ) showing that inclusion of SNPs in the alkoxide gels negatively impacts the gel mechanical properties.…”
Section: Resultssupporting
confidence: 93%
“…The ω = 0.11 gel microstructure was distinctly different with alkoxide aggregates gluing clusters of loosely packed SNPs together. The conclusions of the microstructural analysis was consistent with what was reported previously in similar gels (Mutlu et al, ; Perullini et al, ) and supported the mechanical testing results.…”
Section: Resultssupporting
confidence: 91%
“…In order to improve the optical properties and mechanical stability of these hosts, extension of the precursor concentration range was proposed but it required the addition of cell-protective agents. 23 However, if the encapsulation of more robust organisms, such as algal cells, is targeted, it should be possible to extend the conditions of preparation, and therefore the range of properties, of these nanocomposites while preserving their cytocompatibility. The here-presented screening of the concentration and pH conditions evidences that among the two precursors, silicates play the most prominent role in the kinetics of gel formation, even though it is introduced at concentrations ca.…”
Section: Discussionmentioning
confidence: 99%
“…Noticeably, previous reports on silicate:Ludox hydrogels showed that, at a fixed total silica concentration (2.1 M), the Young's modulus slightly decreases as the relative amount of Ludox increases, which was correlated with the increase in the porous volume. 23 The mechanical properties of tetraethoxysilane:Ludox (HS-40) silica hydrogels were also reported, 58 showing that the mechanical stability of the gel increased with increasing alkoxide content at constant particle concentration. Using larger particles, for a given total silica concentration, the elastic modulus of the gel decreased with increasing particle size.…”
Section: 61mentioning
confidence: 99%
See 1 more Smart Citation